2023
DOI: 10.1002/advs.202300469
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Polypeptide Fused L‐Asparaginase with Mitigated Immunogenicity and Enhanced Efficacy in Treating Hematologic Malignancies

Abstract: L‐Asparaginase (ASP) is well‐known for its excellent efficacy in treating hematological malignancies. Unfortunately, the intrinsic shortcomings of ASP, namely high immunogenicity, severe toxicity, short half‐life, and poor stability, restrict its clinical usage. Poly(ethylene glycol) conjugation (PEGylation) of ASP is an effective strategy to address these issues, but it is not ideal in clinical applications due to complex chemical synthesis procedures, reduced ASP activity after conjugation, and pre‐existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
1
0
Order By: Relevance
“…This approach also resulted in L-ASNase with improved stability, half-life, reduced immunogenicity, in vitro and in vivo anti-cancer activity. In addition, this L-ASNase was more active than the native or PEG-conjugated enzyme [290].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This approach also resulted in L-ASNase with improved stability, half-life, reduced immunogenicity, in vitro and in vivo anti-cancer activity. In addition, this L-ASNase was more active than the native or PEG-conjugated enzyme [290].…”
Section: Discussionmentioning
confidence: 89%
“…Long after injection, the temperature sensitivity of the L-ASNase-ELP chimera resulted in the formation of an in situ depot with sustained release of the enzyme and zero-order release kinetics. In vitro and in vivo studies also showed that compared to L-ASNase and PEG-ASNase, L-ASNase-ELP had higher activity retention, superior stability, longer half-life, lower immunogenicity, lower toxicity and higher potency in vivo and in vitro [290].…”
Section: Prediction Of the Toxicity Of The Proteinmentioning
confidence: 95%
“…The actions of any enzyme should also be tested in vivo to verify its stability, immunogenicity, and antineoplastic properties. Currently, reports from studies in animal models are available only for the commercial enzymes EcAII or ErAII [69][70][71], and there are no data for Nth-hydrolases (class 2) or Rhizobium etli-type (class 3) proteins.…”
Section: Discussionmentioning
confidence: 99%